2017
DOI: 10.17977/um005v1i12017p032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Regular Teachers’ Special Education Pedagogy Competence Level in Elementary and Senior High Inclusive School

Abstract: Comparative Study of Regular Teachers' Special Education Pedagogy Competence Level inInclusive School Elementary and Senior High School Level. In general, this research aims to determine regular teachers' special education pedagogy competence level in the level of elementary and senior high inclusive school. Subject in this research was 38 regular teachers in elementary inclusive school and 45 regular teachers in senior high inclusive school. Data was collected through questionnaire. Data was analyzed by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Not all of them were able to manage the class well because previously the teachers were used to teaching normal children. Teachers who teach in inclusive schools should ideally have special competencies regarding inclusive education and special needs children (Martika & Salim, 2017). Competence is a basic ability that a person must have.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all of them were able to manage the class well because previously the teachers were used to teaching normal children. Teachers who teach in inclusive schools should ideally have special competencies regarding inclusive education and special needs children (Martika & Salim, 2017). Competence is a basic ability that a person must have.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers play an important role in schools to meet the needs and maximize the potential of children with special needs. Teachers who teach in inclusive schools should ideally have special competencies regarding inclusive education and special needs children (Martika & Salim, 2017). The teacher is the main spear in the teaching and learning process to shape attitudes, personality and develop the potential of children without exception.…”
Section: Introductionmentioning
confidence: 99%
“…The level of pedagogical knowledge that teachers in Indonesia have about inclusive educational practices is variable, as gleaned from the few studies in the area. In a study involving 45 teachers, it was found that only two of the regular education teachers had training in inclusive education [20]. The level of knowledge about pedagogical competence in regards to catering for students with special needs was found to be "low".…”
Section: Introductionmentioning
confidence: 98%
“…In a similar study involving 39 teachers, it was found that primary school teachers reported higher levels of pedagogical competence in the area of inclusive education than secondary school teachers. The authors did not provide the relative extent and depth of knowledge held by teachers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the implementation of inclusive education in Indonesia refers to Peraturan Pemerintah No. 70 Tahun 2009(Regulation Government Number 70 Year of 2009, where the children with special needs have education and service which is suitable with their needs in the inclusive education (Martika & Salim, 2017. Inclusive education is the answer of pessimist point of view toward children with special needs, where the peer is the setting to reach equality and participation in inclusive education (Fitriana & Sulthoni, 2017). Peer's positive support, self-esteem support, increasing of academics and social work are the positive impacts of inclusive (Flem & Keller, 2000).…”
Section: Introductionmentioning
confidence: 99%